THE CRYSTAL CHEMISTRY OF MALINKOITE, NABSIO4, AND LISITSYNITE, KBSI2O6, FROM THE KHIBINA-LOVOZERO COMPLEX, KOLA PENINSULA, RUSSIA - Sokolova E.V.; Hawthorne F.C.; Khomyakov A.P. (My University, 2001)
The crystal structure of malinkoite, NaBSiO4, a 13.8964(4) Å, c 7.7001(2) Å, P63, Z = 18, Dx = 2.922 g cm-3, from the Khibina-Lovozero complex, Kola peninsula, Russia, has been solved by direct methods and refined to an R index of 3.8% using 2094 unique observed (|Fo| > 4σF) reflections collected with a single-crystal diffractometer fitted with a CCD detector and MoKα X-radiation. Malinkoite is a framework borosilicate with a structure consisting of six-membered rings of regularly alternating (SiO4) and (BO4) tetrahedra, and Na located in the large channels extending along [001]. There are three unique Si sites, each occupied by Si and each coordinated by four O atoms in a tetrahedral arrangement, with distances of 1.625, 1.622 and 1.622 Å, respectively. There are three unique B sites, each occupied by B and each coordinated by four O atoms in a tetrahedral arrangement, with distances of 1.476, 1.476 and 1.473 Å, respectively. There are five unique Na sites, each completely occupied by Na. Three of the Na sites are [9]-coordinated, with distances of 2.626, 2.642 and 2.630 Å, respectively; the remaining two Na sites are [6]-coordinated, with distances of 2.444 and 2.440 Å, respectively. The (SiO4) and (BO4) tetrahedra link to form six-membered rings of two different configurations based on the following sequences of up (U) and down (D) linkages: UDUDUD and UUDUDD in the ratio of 1:2. Nine-coordinated Na polyhedra are located in big cages formed by stacking of UDUDUD rings. Stacking of UUDUDD rings produces smaller cages occupied by [6]-coordinated Na. In accord with the ratio of two types of rings, there are twelve Na octahedra and six [9]-coordinated Na polyhedra per unit cell in malinkoite. The framework topology is related to that of beryllonite NaBePO4. In the crystal structure of lisitsynite, KBSi2O6, four-membered rings consist of two (SiO4) and two (BO4) tetrahedra, and are linked into zig-zag chains (puckered ladders) along [001]. There are two types of chemically distinct six- and eight-membered rings: (4Si + 2B) and (5Si + B); (5Si + 3B) and (6Si + 2B). Two different pairs of six-membered and eight-membered rings, (4Si + 2B) and (5Si + 3B), and (5Si + B) and (6Si + 2B), respectively, form sheets on (100) and (010). Stacking of sheets and zig-zag chains gives rise to a three-dimensional framework. There are one-dimensional seven-ring channels along the c direction. Lisitsynite, KBSi2O6, and synthetic "boroleucite", K(Si2 B)O6, may be regarded as polymorphs with different patterns of Si-B order.
Keywords: malinkoite; lisitsynite; new mineral species; borosilicate; crystal structure; Khibina; Lovozero; Russia